Developing the s-SAFT-γ Mie equation of state toward nonaqueous alkanolamine-based carbon capture systems - Schulze-Hulbe, Alexander (Stellenbosch : Stellenbosch University, 2024)
Thesis (PhD)--Stellenbosch University, 2024.